Sex Chromosome Turnover in Moths of the Diverse Superfamily Gelechioidea - Carabajal Paladino, Leonela Z.; Provaznıkova, Irena; Berger, Madeleine; Bass, Chris; Aratchige, Nayanie S.; Lopez, Silvia Noemi; Marec, Frantisek; Nguyen, Petr (Oxford University Press, 2019)
Sex chromosomes play a central role in genetics of speciation and their turnover was suggested to promote divergence. Invertebrates, sex chromosome–autosome fusions resulting in neo-sex chromosomes occur frequently in male heterogametic taxa (XX/XY), but are rare in groups with female heterogamety (WZ/ZZ). We examined sex chromosomes of seven pests of the diverse lepidopteran superfamily Gelechioidea and confirmed the presence of neo-sex chromosomes in their karyotypes. Two synteny blocks, which correspond to autosomes 7 (LG7) and 27 (LG27) in the ancestral lepidopteran karyotype exemplified by the linkage map of Biston betularia (Geometridae), were identified as sex-linked in the tomato leafminer, Tuta absoluta (Gelechiidae). Testing for sex-linkage performed in other species revealed that while LG7 fused to sex chromosomes in a common ancestor of all Gelechioidea, the second fusion between the resulting neo-sex chromosome and the other autosome is confined to the tribe Gnoreschemini (Gelechiinae). Our data accentuate an emerging pattern of high incidence of neo-sex chromosomes in Lepidoptera, the largest clade with WZ/ZZ sex chromosome system, which suggest that the paucity of neo-sex chromosomes is not an intrinsic feature of female heterogamety. Furthermore, LG7 contains one of the major clusters of UDP-glucosyltransferases, which are involved in the detoxification of plant secondary metabolites. Sex chromosome evolution in Gelechioidea thus supports an earlier hypothesis postulating that lepidopteran sex chromosome– autosome fusions can be driven by selection for association of Z-linked preference or host-independent isolation genes with larval performance and thus can contribute to ecological specialization and speciation of moths.